THE EFFECTIVENESS OF CORIANDER (Coriandrum sativum L.) EXTRACTS ON REDUCING THE BLOOD SUGAR LEVELS OF ALLOXAN INDUCED WISTAR MALE RATS (Rattus norvegicus L.) - Dersing, Kalvin (JURNAL KEDOKTERAN RAFLESIA, 2020)
AbstractBackground : Diabetes mellitus is the most common metabolic syndrome in the whole world with an incidence of 1-8%. This disease arises when insufficient insulin is produced or insulin cannot function properly.The ability of coriander juice water extract is expected to reduce blood glucose levels because the action is similar to insulin and can stimulate insulin release. Purpose : Knowing effectiveness coriander extract (Coriandrum sativum L.)to decline blood sugar levels in male white rats (Rattus norvegicus L.) wistar strain induced by alloxan. Method : This is a pure experimental study (true-experiment) using a pre and post test design with control group design using subjects namely white rats (Rattus norvegicus L.) male Wistar strain aged 10-12 weeks with a weight of 150-200 grams. By looking at changes in blood sugar levels during administration of alloxan and administration of coriander extract. Results : There were significant changes in some groups induced alloxan (p <0.05), but the effect of coriander extract was not very significant (p> 0.05). Conclusion : Coriander extract can control blood sugar levels to be stable or normal, but it takes longer and more research.  Keywords : coriander extract, blood sugar levels, alloxan